Baltic Salmon and Trout Assessment Working Group (WGBAST) - Bajinskis, Jani; Bernas, Rafal; Dahlgren, Elin; Dannewitz, Johan; Debowski, Piotr; Olesen, Hans Jakob; Kagervall, Anders; Kesler, Martin; Kesminas, Vytautas; Kontautas, Antanas; Leinonen, Tuomas; Lejk, Adam; et al. (ICES, 2023)
The Baltic Salmon and Trout Assessment Working Group [WGBAST] was mandated to assess the status of salmon in Gulf of Bothnia and Main Basin (subdivisions 22–31), Gulf of Finland (Subdivision 32) and sea trout in subdivisions 22–32, and to propose consequent management advices for fisheries in 2022. Salmon in subdivision 22–31 were assessed using Bayesian methodology with a stock projection model (data up to 2022) for evaluating effects of different catch options on the wild river stocks. Section 2 of the report covers catches and other data on salmon in the sea, and summarizes information affecting the fisheries and management of salmon. Section 3 reviews data from salmon spawning rivers, stocking statistics and health issues. Status of salmon stocks in the Baltic Sea is evaluated in Section 4. The same section also covers methodological issues of assessment as well as sampling protocols and data needs for assessment. Section 5 presents data and assessed stock status for sea trout. Since 2022 salmon commercial salmon fishing has been restricted to Bothnian sea and Gulf of Finland. Only recreational salmon trolling in the Baltic Main Basin is allowed and daily bag limit is one adipose fin clipped salmon per day. Since the 1990s, production of wild salmon smolts has gradually increased in the Gulf of Bothnia and Gulf of Finland. For most rivers in Gulf of Bothnia smolt production is predicted to increase slightly in 2024. Long-term trends for smolt production in southern Main Basin rivers have remained stable or slightly decreasing. The current (2022) total wild production in all Baltic Sea rivers is over 3 million smolts, corresponding to about 79% of overall potential smolt production capacity. In addition, about 3.7 million hatchery-reared smolts were released into the Baltic Sea in 2022. Out of 17 analytically assessed wild salmon stocks, 7 have reached MSY level with very high certainty, especially in the northern Baltic Sea. In the Gulf of Finland, wild Estonian rivers show recovery. As assessed previously, ...